Isolasi, karakterisasi dan uji stabilitas pH bakteriofag Xanthomonas oryzae dari area persawahan - Desy Mar’atul Fadlilah; Andree Wijaya Setiawan; Yoga Aji Handoko (Jurnal Ilmiah Pertanian, 2022)
The efforts to increase paddy yields are integrated with disease control. Bacterial Leaf Blight (BLB) is a disease that attacks paddy plants caused by Xanthomonas oryzae bacteria. So far, the control carried out by farmers is by spraying bactericides, planting disease-resistant varieties, and rotating plants that are not pathogenic hosts. However, this method of controlling has not obtained satisfactory results. Therefore, we need an alternative option in overcoming BLB disease, namely using bacteriophages as biocontrol agents in infecting Xanthomonas oryzae bacteria. This study explored the potential of bacteriophages isolated from soil samples near paddy plants' root areas and tested their particle's stability. The stages of experiments were soil sampling, isolation, purification, propagation, and pH stability examination. The results showed that the Xanthomonas oryzae bacteriophages had been isolated, purified, and propagated with the coding Kalibening 1 (XB1), Kalibening (XB2), and Kalibening 3 (XB3). The results of the pH stability test on the three samples also showed that the Xanthomonas oryzae bacteriophages experienced particle instability and the titer tended to drop in the pH range of 3-5, while the Xanthomonas oryzae bacteriophages tended to be stable at neutral and alkaline pH 7-11, particularly XB1 and XB2 bacteriophages.